PHOX2B is a reliable immunomarker in distinguishing peripheral neuroblastic tumours from CNS embryonal tumours. Issue 3 (4th July 2018) - Alexandrescu, Sanda; Paulson, Vera; Dubuc, Adrian; Ligon, Azra; Lidov, Hart G
Abstract : Aims: The PHOX2B gene regulates neuronal maturation in the brain stem nuclei associated with cardiorespiratory function and in the autonomic sympathetic and enteric nervous system. PHOX2B expression is a reliable immunomarker for peripheral neuroblastic tumours; however, no systematic evaluation of central nervous system (CNS) embryonal tumours was included in the studies. We encountered two cases in which the differential diagnosis included neuroblastoma and CNS embryonal tumour, and we hypothesised that PHOX2B immunostain would be helpful in establishing the diagnosis. Methods and results: PHOX2B immunostain was performed on 29 paediatric cases, with adequate controls: one retroperitoneal embryonal tumour in a child with retinoblastoma (index 1), one posterior fossa embryonal tumour in a child with a neuroblastoma (index 2), seven medulloblastomas, four atypical teratoid/rhabdoid tumours (ATRT), four retinoblastomas, six pineoblastomas, four embryonal tumours with multilayered rosettes (ETMR) and two CNS embryonal tumours, not elsewhere classified. Cell lineage immunomarkers (GFAP, OLIG2, synaptophysin, NeuN, CRX, PGP 9.5), immunosurrogates for molecular alterations (beta‐catenin, INI1, Lin‐28), array CGH and OncoPanel were performed as needed. Medulloblastomas, ATRTs, ETMRs, retinoblastomas and CNS embryonal tumours not elsewhere classified were essentially negative for PHOX2B. Two of six pineoblastomas had significant PHOX2B expression, while the rest were negative. Index 1 was negative for PHOX2B and PGP 9.5 and positive for CRX, consistent with retinoblastoma. Index 2 had diffuse PHOX2B expression, MYCN amplification and no copy number changes of medulloblastoma, in keeping with neuroblastoma. Conclusion: PHOX2B antibody is helpful in distinguishing between peripheral neuroblastic and CNS embryonal tumours, which are immunonegative, with the caveat that a subset of pineoblastomas has significant expression.